Study of Stress Induced Failure of the Blood-gas Barrier and the Epithelial-epithelial Cells Connections of the Lung of the Domestic Fowl, Gallus gallus Variant Domesticus after Vascular Perfusion. (January 2013) - Maina, John N.; Jimoh, Sikiru A.
Complete blood-gas barrier breaks (BGBBs) and epithelial-epithelial cells connections breaks (E-ECCBs) were enumerated in the lungs of free range chickens, Gallus gallus variant domesticus after vascular perfusion at different pressures. The E-ECCBs surpassed the BGBBs by a factor of ~2. This showed that the former parts of the gas exchange tissue were structurally weaker or more vulnerable to failure than the latter. The differences in the numbers of BGBBs and E-ECCBs in the different regions of the lung supplied with blood by the 4 main branches of the pulmonary artery (PA) corresponded with the diameters of the blood vessels, the angles at which they bifurcated from the PA, and the positions along the PA where they branched off. Most of the BGBBs and the E-ECCBs occurred in the regions supplied by the accessory- and the caudomedial branches: the former is the narrowest branch and the first blood vessel to separate from the PA while the latter is the most direct extension of the PA and is the widest. The E-ECCBs appeared to separate and fail from tensing of the blood capillary walls, as the perfusion- and intramural pressures increased. Compared to the mammalian lungs on which data are available, i.e., those of the rabbit, the dog, and the horse, the blood-gas barrier of the lung of free range chickens appears to be substantially stronger for its thinness.